Predilection of Teaching Aids Among Year I Medical Students at a Medical College of Mauritius - Mahat, Barun; Limbu, Prakash; Banerjee, Indrajit; Dhungel, Sunil; Das, Pawan Kumar Lal (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Teaching aids are the motivational tool which plays an important role in teaching and learning processes in such a way that it makes the classroom lively, active and interactive. It creates an environment of interest for the students as well as it helps to clarify and understand the subject matter in a better way. The objective of this study is to know the opinion of students regarding the teaching aids among 1st year MBBS students during teaching and learning activities in physiology at SSR Medical College. Methods: The data were collected by pre-designed questionnaire among the 1st year MBBS students of SSR Medical College, Belle Rive, Mauritius. The study was conducted between March and April, 2016. Out of 147 students, 139 students were participated in the study. The data were analyzed using nonparametric test and P values were analyzed by using Chi-Square test. P < 0.05 was considered significant. Results: 60.4% of students thought that the combination of black board and PowerPoint slides was more beneficial compared to blackboard, PowerPoint and whiteboard which were selected by 24.5%, 14.4% and 0.7% respectively. The combination of blackboard and Power Point slides was selected as the most understandable and informative by 51.8% and 64% students respectively. Similarly, the same teaching method was considered the most helpful in retention by 48.2% respondents and most emphatic on important points by 47.5%. More than 50% of the students found the combination of blackboard and Power Point slides as the most captivating (55.4%), interactive (57.6%), providing excellent visual clarity (56.8%), easy for summarization (51.1%) and effective for presentation (56.8%). 46% of the students thought that this combination of teaching aid covered the more topic per lecture. Conclusion: This study shows that the majority of the students preferred combination of aids viz. black board and Power Point for learning and teaching physiology.